Anxiety, depression and coping strategies: Improving the evaluation and the understanding of these dimensions during pre-adolescence and adolescence - Matos, M. G. de.; Tomé, G.; Borges, A. I.; Manso, D.; Ferreira, P.; Ferreira, A. (Journal of Cognitive and Behavioral Psychotherapies, 2008)
The aim of this study is to investigate and refine three different scales which measure depression, anxiety and coping strategies. The relation between these scales is also verified in a non-clinical school population of pre-adolescents and adolescents. Lastly, the moderating effects of age, gender, grade failure and family type are tested. This study used depression, anxiety and coping strategy scales to check moderating effects. The sample consisted of 916 Portuguese pupils, 54.3% females, aged 10 to 22 (M = 14, 44). The participants were randomly selected from the 5th to the 12th grades of public schools. The CDI (Kovacs, 1981), the MASC (March, 1997) and the CRY-Y (Moos, 1993) were used. Scales revealed a good internal consistency and suggested that girls are more anxious than boys are and that older students are more depressed, but use more coping strategies than younger learners. A set of exploratory factorial analyses (EFA) was then carried out with the objective of getting the most representative factor from the anxiety (MASC), the depression /CDI) and the coping (CRY-Y) scales. Reduced scales were identified and they strongly correlated with the previous measures, but better differentiate between a set of moderators. A confirmatory model (CPA) was carried out. Also, adjustment indexes suggested a good fit for the model, but consider both genders separately and the two age groups independently. An analysis of the items retained provided suggestions for school based interventions.